IMPLEMENTASI TEKNIK DEMONSTRASI PADA PEMBELAJARAN FIQH DI SMP IT MAMBA'UL ULUM - Ishmatun Nihayah (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2025)
This study aims to examine the implementation of the demonstration technique in the teaching of Islamic jurisprudence (fiqh) on the topic of funeral prayer for ninth-grade students at SMP IT Mamba’ul Ulum, as well as the challenges faced by the teacher during its application. The study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that the demonstration technique used by the fiqh teacher enhanced students' understanding of the movements and recitations in the funeral prayer. The teacher directly demonstrated the procedures and involved students in the practice. Challenges encountered included limited teaching aids, students’ insufficient memorization of prayer recitations, and a lack of confidence among some students when asked to demonstrate in front of the class. Nevertheless, the teacher addressed these issues creatively, such as by utilizing students as part of the learning media. The demonstration technique proved effective in improving students’ psychomotor skills and made the learning experience more meaningful